2013
DOI: 10.1371/journal.pone.0058471
|View full text |Cite
|
Sign up to set email alerts
|

The miR-183/Taok1 Target Pair Is Implicated in Cochlear Responses to Acoustic Trauma

Abstract: Acoustic trauma, one of the leading causes of sensorineural hearing loss, induces sensory hair cell damage in the cochlea. Identifying the molecular mechanisms involved in regulating sensory hair cell death is critical towards developing effective treatments for preventing hair cell damage. Recently, microRNAs (miRNAs) have been shown to participate in the regulatory mechanisms of inner ear development and homeostasis. However, their involvement in cochlear sensory cell degeneration following acoustic trauma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 93 publications
1
31
0
Order By: Relevance
“…Moreover, it has been reported that miR-183 is upregulated in colorectal cancer, prostate cancer, and hepatocellular carcinomas and downregulated in ovarian cancer, breast cancer stem cells, and osteosarcomas, pointing to varied and cell type-dependent function of miR-183. Several target genes of miR-183 including ITGB1, Taok1, Ezrin, EGR1, PDCD4, and LRP6 have been identified and validated [ 13 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that miR-183 is upregulated in colorectal cancer, prostate cancer, and hepatocellular carcinomas and downregulated in ovarian cancer, breast cancer stem cells, and osteosarcomas, pointing to varied and cell type-dependent function of miR-183. Several target genes of miR-183 including ITGB1, Taok1, Ezrin, EGR1, PDCD4, and LRP6 have been identified and validated [ 13 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al [ 69 ] showed that miR-381-3p promoted chondrogenesis in umbilical cord mesenchymal stem cells through direct suppression of TAOK1 and the downstream Hippo signaling pathway, indicating that TAOK1 may regulate chondrogenesis via the Hippo cascade. In an acoustic trauma study by Patel et al [ 70 ], the downregulation of miRNA-183 and upregulation of TAOK1 were observed in noise-traumatized cochlear cells in rats, indicating that the miR-183/TAOK1 pathway is likely to play a role in sensorineural hearing loss.…”
Section: Tao Kinases In Other Physiological Processes and Diseasesmentioning
confidence: 99%
“…In animals exposed to intense noise, MAPK phosphorylation in the cochlea is altered, ERK1/2 in the sensory and support cells of the cochlear sensory epithelium are activated by phosphorylation; while JNK and p38 MAPKs showed late activation in the SGN, de novo syntheses of the MAPKs are also observed (Meltser et al, 2010 ; Jamesdaniel et al, 2011 ; Maeda et al, 2013 ; Patel et al, 2013 ). Radiation therapy for the treatment of head and neck cancers produces severe ototoxicity due to the increased production of ROS.…”
Section: Intracellular Mechanisms Of Hc Lossmentioning
confidence: 99%